(untitled) (Global Journal of Science Frontier Research, 2011)
In this study Lagos Bar-beach water was distilled using a rectangular solar still. The solar still is a single slope type inclined 22o to the horizontal in the north-south direction. The various chemical and biological parameters of the seawater were analysed before and after distillation. The results showed a total dissolved solid value of 4,014 mg/l and total coliform count of 380 cfu/ml. Thus, Lagos bar-beach water is not suitable for human consumption due to basically high total coliform count far above acceptable maximum limit of 10 cfu/ml. However after the solar distillation zero coliform count and no dissolved solids were recorded. Data generated from the performance evaluation of the solar still over an ambient day time temperature range of between 23-31 °C, and a daily global irradiation range of between 7.5-17.1 MJ m2 that involved physical monitoring of the temperatures of different components of the solar still to determine its efficiency, also validated this result.